A covalent organic framework onion structure. (November 2022) - Zheng, Qi; Li, Xinle; Zhang, Qiubo; Lee, Daewon; Mao, Haiyan; Yang, Chongqing; Bustillo, Karen C.; Reimer, Jeffrey A.; Liu, Yi; Jiang, Jinyang; Zheng, Haimei
Graphical abstract: This paper demonstrates a low-temperature solvothermal method of nitrogen-rich covalent organic framework (COF) onions. The atomic structure and the bonding features are revealed by high resolution transmission electron microscopy (TEM) and electron energy-loss spectroscopy (EELS). The novel COF onion provides potential applications in photocatalysts considering its suitable bandgap value of 2.56 eV. Abstract: Achieving hierarchical nanomaterials from a bottom-up approach remains challenging. Here, we report a closed-cage, onion nanostructure of covalent organic framework (COF) obtained through a low-temperature solvothermal synthesis. Atomic resolution transmission electron microscopy revealed the atomic arrangement in this COF onion, in which rich nitrogen was uniformly embedded in the periodic porous graphitic framework. The COF onion structure displayed graphitic features at a 0.33 nm interlayer spacing with Van der Waals interactions predominated between the layers. The onion layers exhibited significant heterogeneity in layer stacking by adopting a combination of different stacking modes. Defects were also found, such as five- or seven-member rings deviating from the perfect hexagonal lattice. These geometrical defects resulted in curving the 2D layers, which may have promoted the formation of onion nanostructures through a layer-by-layer attachment. We constructed a corresponding model that predicts COF onion properties. This novel onion exhibited a bandgap value of 2.56 eV, resembling other carbon-based nanomaterials, suggesting potential applications in sensors, photocatalysts, and nanoelectronics.